Improving the mechanical properties of MgO-FCC based composite cement for 3D printing - Mok, Zong Han (Nanyang Technological University, 2024)
The utilisation of 3D concrete printing (3DCP) technology has garnered significant interest in the construction industry due to its potential for revolutionizing traditional construction methods. In recent years, MgO-fluid catalytic cracking (MgO-FCC) based cementitious composites have seen an increase in studies to investigate its feasibility to be used as the material for 3DCP printing.